Anthropological proselytism: Reflexive questions for a Hare Krishna ethnography. (December 2013) - Haddon, Malcolm
<x xml:space="preserve">Abstract</x> This paper is an anthropological exegesis on the Hare Krishna theology and practice of sankirtana—a form of proselytisation in which devotees chant the Holy Names of the Lord through city streets and in other public places, and which can also involve other means of 'spreading the word'. This is also an inquiry into the relationship between anthropology and proselytism and their respective modes of communication, a topic I approach reflexively by addressing the awkward methodological question as to whether my writing about Hare Krishna proselytisation is itself a form of proselytisation.